CRISPR Diagnosis and Therapeutics with Single Base Pair Precision. Issue 3 (March 2020) - Lee, Seung Hwan; Park, Young-Ho; Jin, Yeung Bae; Kim, Sun-Uk; Hur, Junho K.
Abstract : Clustered regularly interspaced short palindromic repeats, or CRISPR, has been widely accepted as a versatile genome editing tool with significant potential for medical application. Reliable allele specificity is one of the most critical elements for successful application of this technology to develop high-precision therapeutics and diagnostics. CRISPR-based genome editing tools achieve high-fidelity distinction of single-base differences in target genomic loci by structural identification of CRISPR-associated (Cas) proteins and sequences of the guide RNAs. In this review, we describe the structural features of ribonucleoprotein complex formation by CRISPR proteins and guide RNAs that eventually recognize target DNA sequences. This structural understanding provides the basis for the recent applications of enhanced single-base precision genome editing technologies for effective distinction of specific alleles. Highlights: CRISPR-based genome editing at specific genomic locations is prone to mistargeting other genomic loci with similar DNA sequences. Hence, allele-specific targeting with single base pair precision has become one of the most critical issues of developing CRISPR-based diagnostics and therapeutics for disorders such as genetic diseases and cancer. Understanding the structures of CRISPR proteins in complex with the guide RNAs and the target DNAs facilitated the development of novel methods to distinguish single-base differences. CRISPR technologies are being further enhanced by guide RNA modifications, protein engineering, and the discovery of new CRISPR systems. The advancements in CRISPR enables precise therapeutic targeting of various pathogenic mutations, also high-fidelity diagnostics for detecting low-frequency mutations with single-base precision.